High Speed Low Area DA Based FIR Filter Using EGDI Adder - Kura, Vijetha (International Journal of Integrated Engineering, 2022)
In this paper, we proposed a novel enhanced gate diffusion (EGDI) adder is designed and is implemented in Distributed Arithmetic (DA) based Finite Impulse Response (FIR) filter.  Generally, multipliers, adders, and shift accumulators are the basic blocks present in the FIR filters. The hardware architecture of multipliers is very high. To get rid of this multiplier less architecture is needed in the FIR filter. So Distributed Arithmetic architecture plays a key role in FIR filters which will occupy less area and increase the speed. To reduce the area further the adders in DA are designed using enhanced gate diffusion (EGDI) which increases the operation speed of the FIR filter and at the same time, the area will be decreased. The proposed design is synthesized and implemented in the Synapsis design compiler tool. The area, power delay product, frequency, area delay product, and power of the proposed design are calculated.  When we observe the proposed design has a 15% high-frequency rate when compared with the existing design. Also, the proposed design is more useful in signal, processing applications.